Assessment of Precipitation Data Generated by GPM and TRMM Satellites - Luísa Carolina Silva Lelis; Raoni Wainer Duarte Bosquilia; Sergio Nascimento Duarte (Revista Brasileira de Meteorologia)
Abstract This study aimed to verify the performance of the information produced by the GPM (Global Precipitation Measurement) mission and TRMM (Tropical Rainfall Measurement Mission) on the eastern region of São Paulo state, based on a comparison of rainfall data from DAEE (Department of Waters and Electric Energy of São Paulo State). The comparison was done by comparing spatially aggregated information from both sources. In order to analyze the results, we measured: (1) Relative Difference, (2) BIAS and (3) Root Mean Square Error (RMSE). It was found that the relative differences were in the range of -20% to 20% for both missions. Analyzing the BIAS for both satellites it was observed that 68% of the measurements were overestimated. The highest agreement was obtained for the mesoregion of Campinas and the lowest for Araraquara. In the TRMM, the lowest RMSE values were found in the Araraquara mesoregion and the highest in Piracicaba. In the GPM the closest measured values were observed in the Piracicaba mesoregion, while the most distant values were identified in Araraquara. All the analyzes of this work demonstrated similarity between the errors generated by both satellites. New comparison studies are needed to better understand the products.